Low oxygen: A (tough) way of life for Okavango fishes - Edwards, Thea M.; Mosie, Ineelo J.; Moore, Brandon C.; Lobjoit, Guy; Schiavone, Kelsie; Bachman, Robert E.; Murray-Hudson, Mike (PloS one, 2020)
Botswana’s Okavango Delta is a World Heritage Site and biodiverse wilderness. In 2016–2018, following arrival of the annual flood of rainwater from Angola’s highlands, and using continuous oxygen logging, we documented profound aquatic hypoxia that persisted for 3.5 to 5 months in the river channel. Within these periods, dissolved oxygen rarely exceeded 3 mg/L and dropped below 0.5 mg/L for up to two weeks at a time. Although these dissolved oxygen levels are low enough to qualify parts of the Delta as a dead zone, the region is a biodiversity hotspot, raising the question of how fish survive. In association with the hypoxia, histological samples, collected from native Oreochromis andersonii (threespot tilapia), Coptodon rendalli (redbreast tilapia), and Oreochromis macrochir (greenhead tilapia), exhibited widespread hepatic and splenic inflammation with marked granulocyte infiltration, melanomacrophage aggregates, and ceroid and hemosiderin accumulations. It is likely that direct tissue hypoxia and polycythemia-related iron deposition caused this pathology. We propose that Okavango cichlids respond to extended natural hypoxia by increasing erythrocyte production, but with significant health costs. Our findings highlight seasonal hypoxia as an important recurring stressor, which may limit fishery resilience in the Okavango as concurrent human impacts rise. Moreover, they illustrate how fish might respond to hypoxia elsewhere in the world, where dead zones are becoming more common.